2018
DOI: 10.1038/s41598-018-35373-9
|View full text |Cite
|
Sign up to set email alerts
|

Mutational and phenotypic spectrum of phenylalanine hydroxylase deficiency in Zhejiang Province, China

Abstract: Phenylalanine hydroxylase deficiency (PAHD), one of the genetic disorders resulting in hyperphenylalaninemia, has a complex phenotype with many variants and genotypes among different populations. Here, we describe the mutational and phenotypic spectrum of PAHD in a cohort of 420 patients from neonatal screening between 1999 and 2016. The observed phenotypes comprised 43.57% classic phenylketonuria, 33.10% mild PKU, and 23.33% mild hyperphenylalaninemia, with an overall PAHD incidence of 1 in 20,445. Genetic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
14
8
0
1
Order By: Relevance
“…Patients with BH 4 deficiency were not identified during the study period, which may further confirm the regional differences in PKU typing 12 . Genetic analysis showed that the most common mutation was c.728G>A in the PAH gene, which is in consistent with previous reports 22 , 23 .…”
Section: Discussionsupporting
confidence: 92%
“…Patients with BH 4 deficiency were not identified during the study period, which may further confirm the regional differences in PKU typing 12 . Genetic analysis showed that the most common mutation was c.728G>A in the PAH gene, which is in consistent with previous reports 22 , 23 .…”
Section: Discussionsupporting
confidence: 92%
“…In China, p.Arg241Cys is frequently detected in Taiwanese patients, while p.Arg243Gln is common in both the northern and southern areas of the China mainland, which is consistent with our data [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that the detection rate of p.Arg241Cys in mPKU and MHP patients from southern China was higher than that in other areas [3,27,28]. The results of this study are consistent with those of previous studies [27,28], suggesting that regional and demographic differences may be represented to a certain degree in our study.…”
Section: Discussionsupporting
confidence: 92%
“…This might be due to the higher frequency of the p.Arg53His variant in this region. Finally, the p.Phe392Ile variant was only observed in patients with MHP, in line with the results of previous studies [3,17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation